2018
DOI: 10.20517/2347-8659.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of clinoidal meningiomas: 10 cases analysis

Abstract: The purpose of this article is to advocate standard skull base technique for removing the clinoidal meningioma and to delineate the technique's advantages that aid in achieving an improved extent of tumor resection and enhancing the patients' overall outcome, specially their visual outcome. Methods: A retrospective analysis was performed on 10 consecutive patients with clinoidal meningiomas who underwent surgical resection at the Bangabandhu Sheikh Mujib Medical University and other private clinics between May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In our study, visual improvement was reported in 70% of our patients. In previously published case series in which extradural anterior clinoidectomy was used [2,11,13,[16][17][18][19][20][21][29][30][31], visual improvement ranged from 10 to 77% as shown in Table 4. Preoperative visual status is an important prognostic factor affecting the visual outcome [4,34]; Verma and colleagues reported a 20.7% improvement in visual outcome; however, this study had a higher percentage of patients with long-lasting severe visual deficit (32%) or patients who were already blind (15%) with a mean duration 21.5 months [19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, visual improvement was reported in 70% of our patients. In previously published case series in which extradural anterior clinoidectomy was used [2,11,13,[16][17][18][19][20][21][29][30][31], visual improvement ranged from 10 to 77% as shown in Table 4. Preoperative visual status is an important prognostic factor affecting the visual outcome [4,34]; Verma and colleagues reported a 20.7% improvement in visual outcome; however, this study had a higher percentage of patients with long-lasting severe visual deficit (32%) or patients who were already blind (15%) with a mean duration 21.5 months [19].…”
Section: Discussionmentioning
confidence: 98%
“…Various surgical approaches were advocated in the management of clinoidal meningiomas; the optimum surgical approach to improve the visual outcome and the extent of resection is still debatable. Many studies reported the use of the extradural cranial base technique through pterional approach or FTOZ and anterior clinoidectomy [2,11,13,[16][17][18][19][20][21]. Pterional approach with intradural anterior clinoidectomy [4,[22][23][24][25], lateral supraorbital approach [25][26][27], and lateral sub-frontal approach [13] were also performed in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…An extradural anterior clinoidectomy (EAC) is the most common procedure in most published series [1,2,4,10,12,19,30,34,37,42,48,62,65,68,73,75], and its variant, the intradural anterior clinoidectomy (IAC), has been performed in selected cases by a few authors [5,49,50,55,63,64,70]. EAC also allows the skeletonization of 270° of the optic canal allowing safer removal of the tumor in this region.…”
Section: Clinoidectomy or Not?mentioning
confidence: 99%
“…Meningiomas were named by Harvey Cushing in 1922 and described as common tumors that arise from arachnoid cap cells which form the outer lining of the arachnoid membrane and from related cells such as arachnoid fibroblasts and the meningoblast [1][2][3]. These tumors are generally benign tumors and carry good prognosis.…”
Section: Introductionmentioning
confidence: 99%